Tolerance Level of University Students - Ersanli, Ercumend; Sahin, Canan Guven (South Ukrainian Natl Univ K D Ushynsky, 2017)
In this research, tolerance level of university students was investigated. The experiment involved 919 students of different faculties. The results of the study have shown that female students had lower tolerance levels than male students. Besides, the respondents studying at the scientific departments had higher tolerance levels as compared to those from language and fine arts departments. Additionally, when fine arts and social departments were compared, it became clear that the students of social departments had higher tolerance level. There was no significant difference between other groups. Some recommendations were suggested for increasing the level of tolerance in students.
Keywords: Tolerance; University; Student; Gender; Department